CONTROLLER ACTIONS TO REDUCE LOSS OF ASSETS - Alamsyahbana, Muhammad Isa; Vilistasia, Maria (JURNAL AKUNTANSI FINANCIAL STIE SULTAN AGUNG, 2022)
This study aims to determine the role of the controller in an effort to reduce inventory loss at the Utama Hardware store. The theory used includes agency theory, the role of the controller, and the internal control system. Agency Theory explains how the relationship between company’s owner and management in a company, that some times there was a different goals. This research method is included in qualitative research, using primary data and data obtained through interviews and field observations. The results of this study indicate that the role of a controller in an effort to minimize the risk of losing inventory, namely by implementing an appropriate assessment system for inventory, every purchase and sale of goods will be recorded, checking on incoming goods and outgoing goods, adjusting the order notes for goods with incoming goods, so that if there are errors in incoming goods can be directly informed to the store owner, apply good relations and communication between employees, and implement a control system for goods inventory to carry out supervision in order to reduce the risk of unbalanced goods.Keywords: Controller, Internal Control System, Inventory